Administrative strategies for quality assurance in public universities in Rivers State, Nigeria - Patrick, Judith O. (Communicate: Journal of Library and Information Science, 2025)
The study examined administrative strategies for quality assurance in public universities in Rivers State. Three (3) research questions and three (3) hypotheses were answered and tested in the study respectively. The study adopted descriptive survey design, with a population of three thousand and fifty lecturers, and two thousand four hundred and fifty nonacademic staff drawn from three public universities in Rivers State. The sample of the study comprised of 600 lecturers and 500 administrative staff drawn using the proportionate stratified random sampling technique. The respondents of study responded to a validated 26-item instrument titled “Effective Administrative Strategies for Quality Assurance in Public Universities Questionnaire (EASQAPUQ)”. Mean and standard deviation statistics was used to answer five research questions, while z-test statistics was used to test five null hypotheses at 0.05 level of significance. The findings of the study showed that that there is positive and significant relationship between the mean scores of academic and non-academic university staffs on the influence of planning strategy for quality assurance in public universities in Rivers State (Zcal=1.45; Zcrit=1.96), amongst others. Based on the findings of the study, it was concluded that Based on the findings that effective administrative strategies enhanced quality assurance in public universities in Rivers State. The study recommended that university management should organize a routine administrative training that will impact planning strategies and skills to the academic and non-academic staffs in all the public universities in Rivers State.